2014
DOI: 10.1371/journal.pone.0092281
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Horse Grimace Scale (HGS) as a Pain Assessment Tool in Horses Undergoing Routine Castration

Abstract: BackgroundThe assessment of pain is critical for the welfare of horses, in particular when pain is induced by common management procedures such as castration. Existing pain assessment methods have several limitations, which reduce the applicability in everyday life. Assessment of facial expression changes, as a novel means of pain scoring, may offer numerous advantages and overcome some of these limitations. The objective of this study was to develop and validate a standardised pain scale based on facial expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
479
6
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 436 publications
(517 citation statements)
references
References 32 publications
24
479
6
8
Order By: Relevance
“…These changes in facial expression are similar to those described in other species with respect to pain (Dalla Costa et al, 2014;Keating et al, 2012;Leach et al, 2012;Sotocinal et al, 2011). Importantly, there were no changes in the facial expression of non-lame sheep.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…These changes in facial expression are similar to those described in other species with respect to pain (Dalla Costa et al, 2014;Keating et al, 2012;Leach et al, 2012;Sotocinal et al, 2011). Importantly, there were no changes in the facial expression of non-lame sheep.…”
Section: Discussionsupporting
confidence: 86%
“…Ley et al (1995) also found sheep previously diagnosed with footrot were still showing an increased response to mechanical stimulation compared to control sheep three months after they had seemingly recovered. Control sheep were also not scored as zero on day 0 or day 90, a finding observed in other studies using facial expression as a pain scoring system (Dalla Costa et al, 2014;Keating et al, 2012). There are several possible explanations for this.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations